Οργανωτική Επιτροπή, συνδιοργάνωση Σχολής Επιστημών Υγείας, ΤΕΠΑΚ και Ιατρικών Υπηρεσιών και Υπηρεσιών ∆ημόσιας Υγείας, Υπουργείου Υγείας - Middleton, Nicos (My University, 2026)
Memorandum of Understanding for the partnership of the Cyprus University of Technology and Ministry of Health for the promotion of the WHO Health Cities programme in Cyprus, which contributed to the establishment and activation of the first National Network of Health Cities in Cyprus with the participation of 9 municipalities